THE IMPACT OF APPLYING ENGLISH CHATS OF WHATSAPP APPLICATION ON STUDENTS’ ENGLISH VOCABULARY MASTERY - Iradatullah Suhadi; Ahmad Talib; Ryan Rayhana Sofyan (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2024)
This study aims to determine the impact of applying English chat on students' English vocabulary mastery through the WhatsApp application. It employs a qualitative research method with a qualitative descriptive design involving 10 students. Data collection techniques include observation, interviews, and documentation. The study reveals several impacts on students' English vocabulary mastery as a result of using English chats on WhatsApp, including improvements in word meaning, contextual usage, spelling, pronunciation, and understanding of word forms. However, there is a noted limitation regarding pronunciation development due to the nature of WhatsApp as a communication application, suggesting that face-to-face learning may be more effective in this aspect. Students perceive the impact of using English chats on WhatsApp positively, as they enjoy the learning experience and find teachers responsive to their questions. WhatsApp is regarded as a user-friendly application with potential educational benefits, accessible anytime and anywhere.